Identifying and Regulating the Environmental Risks in the Development and Utilization of Natural Gas as a Low-Carbon Energy Source - Fu, Jiaxin; Liu, Yingqi; Sun, FeiHong (Frontiers in Energy Research, 2021)
In response to climate change and energy transition, natural gas has been rapidly developed as a relatively low-carbon energy source by the Chinese government. However, there remain environmental risks at different stages in the entire process from development to utilization. Firstly, this article identifies various environmental risks and benefits of natural gas along the entire industry chain from upstream development, midstream transportation, to downstream utilization. It is found that during upstream development, extraction activities could affect land use, wildlife, and water consumption, as well as causing air pollution and water pollution. Of all the activities at this stage, hydraulic fracturing has the worst environmental impact. During the midstream storage and transportation stage, methane leakage is the biggest environmental risk. In the downstream combustion and utilization stage, the risk of harm to the environment is less than other energy sources, although there are some greenhouse gas effect and water pollution issues. Secondly, this article puts forward some policy recommendations to mitigate upstream hydraulic fracturing, to optimize natural gas storage and transportation monitoring systems, and to promote technologies for efficient utilization of natural gas.